ANALYSIS OF THE EFFECT OF RETURN AND SHARE TRADING VOLUME OF SHARES OF BID-ASK SPREAD PRE-AND POST-ANNOUNCEMENT OF THE FINANCIAL STATEMENTS AT LQ 45 - Supardi, Supardi (Accounting, 2010)
Trade system with the auction system, the Jakarta Stock Exchange closely related to the ask price and bid-ask price within reach price agreement. The purpose of this study was to determine whether there are differences significantly influence stock returns and trading volume of shares on the bid-ask spread pre-and post-announcement of financial statements in good condition news. The secondary method which consists of data collection using data from the method of the document and judgment sampling methods, and are used as sample of stocks of 35 companies included LQ45 in the January 2004 until Februari 2002. Sources of data obtained from the Indonesian Capital Directory Marker, JSX Monthly Statistics, PPAUGM, MM UGM databases, and other relevant sources. Sources of data obtained from the Indonesian Capital Directory Marker, JSX Monthly Statistics, PPAUGM, MM UGM databases, and other relevant sources. The data analysis technique used is multiple regression analysis, paired t-test and chow. In processing the data using SPSS version 10.The results showed that there was no difference in the effect of stock return and trading volume of shares on the bid-ask spread pre-and post-announcement of the financial statements. One possible cause is the perception thet the financial statements do not provide enough information can be trusted as a base collection decisions, because the information has a low appreciation of the independence of the independence of public accountants. Keyword : Trade, Exchange, Financial